2000
DOI: 10.1002/chin.200020136
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Synthesis and in vitro and in vivo Functional Studies of ortho‐Substituted Phenylpiperazine and N‐Substituted 4‐N‐(o‐Methoxyphenyl)aminopiperidine Analogues of WAY100635.

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…The WAY 100,635 doses (0.1, 1.0 mg/kg, i.p.) were selected from prior studies demonstrating efficacy against thermoregulatory disruption produced by 8-OH-DPAT in rats (Mensonides-Harsema et al, 2000;Nicholas and Seiden, 2003).…”
Section: Drugsmentioning
confidence: 99%
“…The WAY 100,635 doses (0.1, 1.0 mg/kg, i.p.) were selected from prior studies demonstrating efficacy against thermoregulatory disruption produced by 8-OH-DPAT in rats (Mensonides-Harsema et al, 2000;Nicholas and Seiden, 2003).…”
Section: Drugsmentioning
confidence: 99%
“…20,67,87 With continued efforts, a novel analog of WAY-100635 with O-mesyl was prepared and found to have a high apparent affinity to 5-HT 1A receptors with an IC 50 of 7.25 nM that measured as the displacement of [ 3 H]8-OH-DPAT from rat frontal cortex. 88 The radioligand [ 11 C]MWAY ([ 11 C]4, Figure 3) was successfully prepared using [ 11 C]mesyl chloride in a high radiochemical yield of 95% (decay corrected). 89 However, PET studies with this radioligand have not been reported yet.…”
Section: Pet Ligands For 5-ht 1a Receptorsmentioning
confidence: 99%
“…9,10 Within the family of aminergic GPCR ligands, 1,4disubstituted aromatic piperidines and piperazines (1,4-DAPs, Figure 1) 11 are known as privileged structural moieties simulating endogenous neurotransmitters including dopamine, serotonin, and (nor)epinephrine. Representative examples of this huge family of bioactive compounds are the CNS active drug haloperidol, the drug candidates WAY-100635, 12 BP 897, 13 and the recently discovered 2-pyridinylmethylamine derivative befiradol (F-13640), a highly selective 5-HT 1A receptor agonist that shows remarkable effects and is currently undergoing clinical trials for the treatment of severe, chronic pain. 10,[14][15][16] Befiradol shows high binding affinity and selectivity as well as strong partial agonist properties in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…Showing a fast onset of action and high intrinsic activity, the 5-HT 1A receptor can be activated to produce maximally effective antidepressant-like activity, opening new perspectives for the treatment of depressive disorders. There is strong evidence that the target protein 5-HT 1A can be also addressed for the treatment of further central nervous system (CNS) disorders including tardive dyskinesia and neuropathic pain. , Within the family of aminergic GPCR ligands, 1,4-disubstituted aromatic piperidines and piperazines (1,4-DAPs, Figure ) are known as privileged structural moieties simulating endogenous neurotransmitters including dopamine, serotonin, and (nor)epinephrine. Representative examples of this huge family of bioactive compounds are the CNS active drug haloperidol, the drug candidates WAY-100635, BP 897, and the recently discovered 2-pyridinylmethylamine derivative befiradol (F-13640), a highly selective 5-HT 1A receptor agonist that shows remarkable effects and is currently undergoing clinical trials for the treatment of severe, chronic pain. , Befiradol shows high binding affinity and selectivity as well as strong partial agonist properties in vitro. As an example, subtype selectivity over 5-HT 1B was shown to be greater than 10 000 .…”
Section: Introductionmentioning
confidence: 99%